Extracting Indigenous Riau-Malays’ Scientific Literacy through Lancang Kuning Folklore with Thematic Learning in the Primary School Context - Neni Hermita; Mahmud Alpusari; Jesi Alexander Alim; Elfis Suanto (STKIP Singkawang, 2020)
This research aims to extract the story or take the essence from folklore the Lancang Kuning its scientific literacy value for thematic learning in primary school. Scientific literacy is an understanding of science and its application to the needs of the community. The method used is the descriptive qualitative analysis of interviews and documentation strategies and evaluation of data. Results from this research that obtain it some value in scientific literacy in the people story Lancang Kuning text that can then be applied in teaching in primary school using thematic learning. From these results, it can be concluded that since time immemorial been their aspects of scientific literacy are taught parents to their children either through folklore or of other matters related to culture.